Fuzzy Logic PSS Assisted by Neighboring Signals to Mitigate the Electromechanical Wave Propagation in Power Systems - Mahmoud N. Ali (Institute of Advanced Engineering and Science, 2015)
This paper deals with the mitigation of electromechanical wave propagation in power systems. Different conventional controllers addressed this problem, such as the conventional PSS and the conventional fuzzy logic PSS. In this paper, the fuzzy logic PSS is assisted by auxiliary signals from the fuzzy logic PSS of the interconnected machines to augment the damping of electromechanical wave propagation and the associated oscillations. The neighboring machines speed deviation and its derivatives signals are exploited through the fuzzy logic PSS to assist the local fuzzy logic PSS. The disturbance propagation and reflection phenomena are considered in the design of the adopted strategy. The efficacy of the proposed assistance of the conventional fuzzy logic PSS are examined through different simulation results. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7837